MODERN WAYS TO INCREASE MOTIVATION IN TEACHING FOREIGN LANGUAGE READING AT THE SECONDARY LEVEL - Shamsiyeva Xolida Sharobiddin qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: The article analyzes modern methods and strategies that can be employed to increase motivation in teaching foreign language reading at the secondary level. Also, it identifies effective, research-based approaches that engage students in the reading process, enhance their language acquisition, and foster a long-term interest in foreign language learning.